Ultrasonographic findings in diabetic cheiroarthropathy: a pilot study - Löffler, Christian; Leipe, Jan; Hellmich, Bernhard (Scandinavian journal of rheumatology, 2024)
Diabetic cheiroarthropathy (DCA) is one of the musculoskeletal manifestations of diabetes mellitus. It is clinically diagnosed using the prayer and tabletop signs. The clinical appearance, however, mimics autoimmune-mediated polyarthritis of the hands and fingers. It is therefore crucial to positively identify DCA patients. We used high-frequency B-mode ultrasound to investigate 14 patients with DCA and seven non-DCA diabetics with anti-cyclic citrullinated peptide antibody-positive rheumatoid arthritis (RA). We recorded the frequency of synovitis in radiocarpal, metacarpophalangeal, and proximal interphalangeal joints, the presence of tenosynovitis of the finger flexor tendons, echogenicity of the synovia and the flexor tendon sheaths, and soft tissue alterations in the digits. We compared our findings between groups to determine sonographic characteristics of DCA. A low rate of small finger joint involvement in the presence of a high rate of finger flexor tendinopathy showed a high association with DCA in correlation (p = 0.002) and regression analysis (p < 0.001). Tendon sheaths were significantly more often hyperechoic and proliferative in DCA compared to RA (p = 0.008), and hypoechoic soft tissue alterations were almost exclusively seen in DCA patients (p = 0.003). Radiocarpal joint involvement and its echogenicity did not differ between groups. Ultrasonography shows typical features in DCA, and is capable of discriminating DCA from non-DCA patients with RA and diabetes.